Health of elderly parents, their children's labor supply, and the role of migrant care workers - Wolfgang Frimmel; Martin Halla; Jörg Paetzold; Julia Schmieder (Johannes Kepler University of Linz, Department of Economics, 2021)
We estimate the impact of parental health on adult children's labor market outcomes. We focus on health shocks that increase care dependency abruptly. Our estimation strategy exploits the variation in the timing of shocks across treated families. Empirical results based on Austrian administrative data show a significant negative impact on the labor market activities of children. This effect is more pronounced for daughters and for children who live close to their parents. Further analyses suggest informal caregiving as the most likely mechanism. Finally, we exploit a liberalization of the formal care market, which led to a sharp increase in the supply of foreign care workers. This reform significantly reduced the negative effect of a parental health shock on their children's labor market outcomes.
Keywords: J14; J22; I11; I18; R23; 330; Informal care; formalcare; aging; health; laborsupply; labormigration